The Evolution and Future Prospects of BLIK: A Case Study - Kubiczek, Jakub; Czarkowska, Marta (Ewolucja i przyszłość BLIK-a: studium przypadku, 2024)
Aim: This paper aims to outline the development prospects of BLIK, examining the key factors influencing its growth. By analysing the drivers of BLIK’s expansion, the paper highlights its rise as a major player in the payment sector. Methodology: A thematic literature review and secondary data analysis, including data from the National Bank of Poland [Narodowy Bank Polski] and findings from scientific studies and industry reports, were utilised to fulfill the research aim. The discussion of BLIK’s advantages was structured using a functional model of payment execution. Findings: BLIK’s effective marketing strategy and robust informational-promotional efforts have propelled its expansion within the Polish payment market. The primary limitation for BLIK users is the requirement for a smartphone and digital proficiency, presenting a barrier for digitally excluded individuals. Nonetheless, analysis suggests BLIK’s position in Poland will continue to strengthen, with expansion into foreign markets evidenced by the adaptation of select international terminals to accept BLIK payments. Implications: BLIK’s increasing popularity is reshaping consumer payment preferences, helping businesses attract Polish customers, and prompting financial institutions to adapt their services and infrastructure to meet evolving market demands. Originality/value: This paper’s unique contribution is its analysis of the key factors behind BLIK’s rise, underscoring its significant impact on the payment sector.
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 2, s. 1-13
Keywords: BLIK; PayTech; payment innovations; payment scheme; payment systems; innowacje płatnicze; schemat płatniczy; system płatności